ISU-ISU STRATEGIS DALAM PEMBANGUNAN PENDIDIKAN NASIONAL DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INGGRIS - IRWANDI, IRWANDI (Pelita Bangsa Pelestari Pancasila, 2018)
There are actual issues in education in Indonesia nationally. These issues include cha-racter education, National Examination, curriculum changing, teachers’ competency inwritingscientific papers, educational infrastructure, and education management. The issues on character education are more emphasized on strategies for character education to be right on target. While the issue of National Exam focuses on the essence of implementation. The last three issues relate to the urgency of teachers’ scientific work, instructional media, and the arrangement of recruitment, career development, and teacher supervision system. All the above national education issues have implications for learning English as a foreign language in Indonesia. This article discusses issues of national education and its implications for learning English in foreign languages in Indonesia.